Progres Ekonomi Masyarakat Penerima Program Keluarga Harapan di Desa Tomini Utara Kecamatan Tomini Kabupaten Parigi Moutong - Ariansyah, Randy; Alimuddin, Nurwahida; Samsinas, Samsinas (Journal of Islamic Community and Development, 2025)
This study aims to examine the implementation and economic progress of beneficiaries of the Family Hope Program (PKH) in Tomini Utara Village, Tomini Sub-district, Parigi Moutong Regency. The method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results show that the implementation of PKH is fairly good but has not yet achieved its optimal goals. Identified issues include mistargeted aid distribution and a lack of information provided to recipients regarding data changes. Economically, there has been progress such as meeting basic needs, home renovations, purchasing farmland, and starting small businesses. Suggestions are given to program implementers to improve targeting and communication, and to beneficiaries to be more proactive in seeking information. Future researchers are encouraged to explore this topic further from different perspectives.